Transcanal endoscopic treatment for congenital middle ear cholesteatoma in children. Issue 29 (22nd July 2022) - Zeng, Nan; Liang, Meng; Yan, Shang; Zhang, Lue; Li, Shuo; Yang, Qiong
Abstract : To investigate the feasibility and efficacy of transcanal endoscopic treatment for congenital middle ear cholesteatoma in children. Eleven children diagnosed with congenital middle ear cholesteatoma, who underwent total ear endoscopic surgery under general anesthesia, were included from the Huazhong University of Science and Technology Union Shenzhen Hospital between January 2016 and December 2020. We retrospectively analyzed their operation process and surgical complications through the surgical video; moreover, we compared the pre- and postoperative hearing outcomes. One child underwent a planned second operation to reconstruct the ossicular chain. At 6 postoperative months, all 11 children underwent reexamination. There was no significant change and a significant decrease in the mean bone and air conduction hearing thresholds, respectively ( P > .05 and P < .05); moreover, there was a significant reduction in the air–bone conduction difference ( P < .05). Further, the air–bone conduction difference was reduced to >20 dB and >10 dB in 11 and 7 children, respectively. Follow-up of the children did not reveal sensorineural deafness, facial paralysis, and other serious complications; further, there were no cases of recurrence. Transcanal endoscopic treatment for congenital middle ear cholesteatoma in children is feasible, minimally invasive, and functional.